Adipocyte-like signature in ovarian cancer minimal residual disease identifies metabolic vulnerabilities of tumor initiating cells - Artibani, M; Masuda, K; Hu, Z; Rauher, PC; Mallett, G; Wietek, N; Morotti, M; Chong, K; KaramiNejadRanjbar, M; Zois, CE; Dhar, S; El-Sahhar, S; et al. (American Society for Clinical Investigation, 2021)
Similar to tumor initiating cells (TICs), minimal residual disease (MRD) is capable of re-initiating tumors and causing recurrence. However, the molecular characteristics of solid tumor MRD cells and drivers of their survival have remained elusive. Here we performed dense multi-region transcriptomics analysis of paired biopsies from 17 ovarian cancer patients before and after chemotherapy. We reveal that while MRD cells share important molecular signatures with TICs, they are also characterized by an adipocyte-like gene expression signature and a portion of them had undergone epithelial-mesenchymal transition (EMT). In a cell culture MRD model, MRD-mimic cells show the same phenotype and are dependent on fatty acid oxidation for survival and resistance to cytotoxic agents. These findings identify EMT and FAO as attractive targets to eradicate MRD in ovarian cancer and make a compelling case for the further testing of FAO inhibitors in treating MRD.